Cien Años de Microglía: Milestones in a Century of Microglial Research. Issue 11 (November 2019) - Sierra, Amanda; Paolicelli, Rosa C.; Kettenmann, Helmut
Abstract : The year 2019 marks the 100-year anniversary of the discovery of microglia by Pío del Río-Hortega. We will recount the state of neuroscience research at the beginning of the 20th century and the heated scientific dispute regarding microglial identity. We will then walk through some of the milestones of microglial research in the decades since then. In the last 20 years, the field has grown exponentially. Researchers have shown that microglia are unlike any other resident macrophages: they have a unique origin and distinguishing features. Microglia are extraordinarily motile cells and constantly survey their environment, interacting with neurons, astrocytes, oligodendrocytes, neural stem cells, and infiltrating immune cells. We finally highlight some open questions for future research regarding microglia's identity, population dynamics, and dual (beneficial and detrimental) role in pathology. Highlights: Microglia were first described by the Spanish researcher Pío del Río-Hortega in 1919. Río-Hortega's discoveries identified and defined the three types of glial cells of the CNS: astrocytes, oligodendrocytes, and microglia. The field stagnated until the 1960s, when Georg Kreutzberg discovered the role of microglia in synaptic stripping in pathology. Microglia were subsequently characterized as pathologic sensors in essentially all brain diseases and orchestrators of the neuroinflammatory response. In the last two decades, after the discovery of their extraordinary motility and their unique origin in the yolk sac, microglial research has grown exponentially. Physiological roles of microglia include synapse monitoring and pruning, as well as modulating neurogenesis, myelination, and vasculogenesis.